Molecular Determinants of Protein Pathogenicity at the Single‐Aggregate Level - Agnieszka Urbanek; Emma F. Garland; Emily E. Prescott; Marianne C. King; Anna Olerinyova; Hollie E. Wareing; Nia Georgieva; Ellie L. Bradshaw; Svetomir B. Tzokov; Alexander Knight; Alexander I. Tartakovskii; Tarja Malm; et al. (Advanced Science)
Abstract Determining the structure‐function relationships of protein aggregates is a fundamental challenge in biology. These aggregates, whether formed in vitro, within cells, or in living organisms, present significant heterogeneity in their molecular features such as size, structure, and composition, making it difficult to determine how their structure influences their functions. Interpreting how these molecular features translate into functional roles is crucial for understanding cellular homeostasis and the pathogenesis of various debilitating diseases like Alzheimer's and Parkinson's. In this study, a bottom‐up approach is introduced to explore how variations in protein aggregates’ size, composition, post‐translational modifications and point mutations profoundly influence their biological functions. Applying this method to Alzheimer's and Parkinson's associated proteins, novel disease‐relevant pathways are uncovered, demonstrating how subtle alterations in composition and morphology can shift the balance between healthy and pathological states. This findings provide deeper insights into the molecular basis of protein's functions at the single‐aggregate level, enhancing the knowledge of their roles in health and disease.